Pengaruh Kualitas Pelayanan, Citra Merek dan Getok Tular terhadap Keputusan Pembelian Jasa - Dewi Kurniasih; Elizabeth Elizabeth (Penerbit Goodwood, 2021)
Purpose: This study aimed to analyze the effect of service quality, brand image and word of mouth on service purchase decisions. Research methodology: This type of research was descriptive. The population used in this study were all customers at Lion Parcel Kreo Branch, totaling 2,089 customers from July 2019 to September 2019. The sample used was 100 respondents, with the sampling method using probability sampling with a simple random sampling technique. Data were collected using a questionnaire and then the data were further analyzed using SPSS (Statistical Product and Service Solutions) version 20. Data analysis was performed on the Validity Test, Reliability Test, Classical Assumption Test (Normality Test, Multicollinearity Test, Heteroscedasticity Test), Correlation, Test Hypothesis (t test and F test), Coefficient of Determination and Multiple Linear Regression Analysis. Results: The results showed that, the quality of service, brand image and impact on the purchase decision of services.